Penambahan Semen Sebagai Filler Pada Campuran AC WC Pada Kadar Aspal Optimum Untuk Meningkatkan Stabilitas - Ni Ketut Ana Erawati; Putu Ariawan; I Komang Agus Ariana; Putu Budiarnaya (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Roads as one of the supporting transportation processes are very important for the progress and welfare of society. By seeing the very high increase in population mobility, it is necessary to increase both the quantity and quality of roads that meet the needs of society. AC-WC asphalt concrete is a mixture used as a pavement consisting of coarse aggregate, fine aggregate, filler and asphalt whose proportions have been determined. The layer must later have waterproof properties, structural value and strong (durable).This study aims to determine the characteristics of Marshall values ​​at optimum asphalt content of AC – WC mixture using Portland Cement filler. This study was conducted by Marshall testing which was divided into two stages. The first stage was 45 test objects and the second stage of research was 9 test objects with variations in filler percentage added, namely 1%, 1.5%, and 2%. The asphalt content used in this study was 4.5%, 5.0%, 5.5%, 6.0%, 6.5%.From this study, the optimum asphalt content (5.8%) was obtained. The Marshall characteristics used were Specific Gravity, VIM (Void In Mix), VMA (Void In Mineral Aggregate), VFB (Void Fallid With Bitumen), Stability, Flow and MQ (Marshall Quotient). The test results proved that the addition of Portland Cement filler to the AC WC mixture at the optimum asphalt content resulted in an increase in the stability value.From Marshall's test on the stability value at the variation of filler percentage of 1.0%, 1.5%, 2.0% at the optimum asphalt content continues to increase. The stability value at the optimum asphalt content with the addition of 1.0% filler obtained an average value of 1025.3, a mixture with 1.5% filler 1090.9 kg, a mixture with 2.0% filler 1115.5 kg. The stability value obtained is also still within the standard specification limit of Bina Marga, which is min 800 kg.